TSSFinder—fast and accurate ab initio prediction of the core promoter in eukaryotic genomes. Issue 6 (31st May 2021) - de Medeiros Oliveira, Mauro; Bonadio, Igor; Lie de Melo, Alicia; Mendes Souza, Glaucia; Durham, Alan Mitchell
Abstract: Promoter annotation is an important task in the analysis of a genome. One of the main challenges for this task is locating the border between the promoter region and the transcribing region of the gene, the transcription start site (TSS). The TSS is the reference point to delimit the DNA sequence responsible for the assembly of the transcribing complex. As the same gene can have more than one TSS, so to delimit the promoter region, it is important to locate the closest TSS to the site of the beginning of the translation. This paper presents TSSFinder, a new software for the prediction of the TSS signal of eukaryotic genes that is significantly more accurate than other available software. We currently are the only application to offer pre-trained models for six different eukaryotic organisms: Arabidopsis thaliana, Drosophila melanogaster, Gallus gallus, Homo sapiens, Oryza sativa and Saccharomyces cerevisiae . Additionally, our software can be easily customized for specific organisms using only 125 DNA sequences with a validated TSS signal and corresponding genomic locations as a training set. TSSFinder is a valuable new tool for the annotation of genomes. TSSFinder source code and docker container can be downloaded from http://tssfinder.github.io . Alternatively, TSSFinder is also available as a web service at http://sucest-fun.org/wsapp/tssfinder/ .